Project control: an exploratory study of levers of control in the context of managing projects. Issue 4 (7th November 2016) - Rezania, Davar; Baker, Ron; Burga, Ruben
Abstract : Purpose: This paper aims to examine the levers of control (LOC) framework in the context of managing projects. The authors explore the impact of diagnostic systems, interactive systems, beliefs systems and boundary systems on project performance and explore the association between control levers. Design/methodology/approach: Using data gathered from 113 project managers representing 38 organizations, the authors used the partial least squares path modelling algorithm to analyse the data. Findings: The analysis validates the LOC framework in the context of managing projects and reveals the interrelatedness of control systems and their impact on project performance. Research limitations/implications: The conclusions support the current emphasis on performance reporting and change control and highlight the need to consider the interdependencies between control levers. Originality/value: This study re-conceptualizes project control by using the LOC framework in the context of managing projects as temporary organizations. This provides a model for investigating and understanding project management control systems that consider the interaction of control mechanisms. Furthermore, the associations between the four control systems and project performance are examined, rather than individual mechanisms in isolation.